Love, culture, and well-being: How values moderate the link between relationship status and well-being across 57 countries - Śmieja, M.; Walczak, A.; Cacek, J.; Górski, M. R.; Bond, M. H.; Gjoneska, B.; Hussain, M. A.; Joshanloo, M.; Szumowska, E.; Teyssier, J.; Yeung, V. W. L.; Haas, B. W.; et al. (International Journal of Intercultural Relations, 2025)
This study examines the interplay between relationship status, well-being, and values across 57 countries. We hypothesized that individuals in romantic relationships would report higher well-being (measured as happiness, harmony, and meaning in life) compared to singles. We anticipated that in cultures prioritizing relationships, the benefits of being coupled would be amplified, while in societies emphasizing autonomy, the well-being gap would diminish. Specifically, we posited that values prevalent in WEIRD societies (Western, Educated, Industrialized, Rich, and Democratic)–such as self-direction and achievement–would positively moderate the association between relationship status and well-being, whereas values characteristic of non-WEIRD societies–such as tradition and conformity–would have a negative moderating effect. Our findings support that coupled individuals generally report higher well-being; however, the moderating effects of cultural values were more complex than expected. Cultural classifications of WEIRD and non-WEIRD did not consistently explain the well-being gap. Interestingly, in cultures emphasizing conformity, single and coupled individuals both reported greater meaning, leading to an overall decrease in the well-being gap. Conversely, higher self-direction values were associated with a wider well-being gap, with singles experiencing decreased happiness and meaning. These findings suggest that values such as conformity and self-direction exert domain-specific effects on well-being, influenced by broader social context and individual perceptions. Our research highlights the necessity of integrating cultural and individual factors in well-being research to achieve a more nuanced understanding of the quality of life for singles and those in relationships.